Relationship Of Knowledge And Attitudes With Self-Awareness In Implementing Health Protocols In Central Cilacap Subdistrict Post-Pandemic Covid-19 - Yuliyanti, Salfina (Journal of International Multidisciplinary Research, 2025)
This research article aims to discover the relationship of knowledge and attitudes with self-awareness in implementing health protocol in Cilacap sub-district Post-pandemic. This research is a type of analytical research and the design used in this research is cross sectional. This research uses primary data and secondary data. Samples were 112 people. The instrument used was a structured questionnaire. Data were analyzed with chi-square test. Results showed that knowledge OR; 2,918 95% Cl=(1,306-6,522), attitude OR; 2,293 95% Cl=(1,305-5,083), were knowledge and attitude are associated with self awareness in implementing health protocols.